LINGKUNGAN PENDIDIKAN ISLAM PADA GENERASI MILENIAL DI ERA GLOBALISASI - Yusuf, Budi; Alpata, Ahmad Rudi; Farhan, Farhan (Al-Ulum: Jurnal Pendidikan Islam, 2024)
This study explores of the environment on Islamic education for the millennial generation in the era of globalization. The main issue addressed is how globalization and technology affect the Islamic education process. The research aims to investigate the impact of social and technological environments on the understanding and practice of religious values among millennials. The study employs a qualitative approach with literature analysis and relevant case studies. The findings indicate that millennials face significant challenges in distinguishing between traditional and modern values. Technology and social media play crucial roles in accessing and disseminating religious information, but they can also cause identity confusion and value shifts. Therefore, Islamic education needs to adapt new approaches relevant to the dynamics of globalization to maintain the essence of Islamic teachings.